Mapping the Futures of Islamic Philanthropy: A Bibliometric Analysis of Global Trends and its Foresight Directions - Anggara, Fajar Surya Ari; Faradisi, Roghiebah Jadwa (ASFA Foundation, 2025)
Lack of literature integrating trend analysis with foresight to plan Islamic philanthropy's future and bibliometric analysis. How has worldwide Islamic philanthropy intellectuality changed? What emerging trends and orientations may bibliometric analysis reveal? This study uses mixed approaches. This study uses quantitative bibliometrics and qualitative content analysis to examine Islamic philanthropy's intellectual environment. This study searches Scopus for